An empirical study on the relationship between emotional labor and work performance among university teachers - Hao, Danna (Frontiers in Psychology, 2024)
This study is based on the theory of emotional events and explores the relationship between emotional labor and the job performance of university teachers. Relevant data was obtained through a questionnaire, and a structural equation model was constructed for path analysis. The study found that the surface performance of university teachers has a significant negative impact on relationship performance and task performance; Deep performance and proactive authenticity of university teachers have a significant positive impact on relationship performance, task performance, and adaptability performance, respectively; The passive reality of university teachers has a significant negative impact on relationship performance, task performance, and adaptability performance. Based on research findings, this study proposes suggestions for the performance evaluation mechanism of university teachers, including improving the recruitment methods, increasing the emotional labor assessment and incentive mechanism, focusing on alleviating negative emotions of teachers, strengthening the awareness guidance and education of school management and teachers on emotional labor, establishing training courses on emotional labor for teachers, arranging various activities reasonably, and creating a good working atmosphere. Ultimately, these suggestions aim to help university teachers recognize the significance of emotional labor, promote their educational and teaching work, and provide new methods and paths for improving the work performance of university teachers.